Sexualized labour in digital culture: Instagram influencers, porn chic and the monetization of attention. Issue 1 (24th April 2019) - Drenten, Jenna; Gurrieri, Lauren; Tyler, Meagan
Abstract : The rise of digital technologies and social media platforms has been linked to changing forms of work, as well as the mainstreaming of pornography and a 'porn chic' aesthetic. This article examines some of the ways in which these themes coalesce, and interrogates the conceptual boundaries of sexualized labour, extending beyond traditional organizational settings and into Web 2.0. The study explores performances of sexualized labour on social media by analysing visual and textual content from 172 female influencers on Instagram. This article contributes to the literature on sexualized labour in three ways. First, by demonstrating how sexualized labour is enacted across various forms of influencer labour, and how this relates to the attention economy and monetization. Second, by developing the extant conceptualization of sexualized labour and introducing connective labour as a required element to mobilize sexualized labour. Third, by opening up a critical analysis of what is meant by 'sexualized' labour within a cultural context of pornographication.